Effects of Sr substitution for Ba on dielectric and energy-storage properties of SrO-BaO-K2O-Nb2O5-SiO2 glass-ceramics. Issue 13 (October 2017) - Wang, Haitao; Liu, Jinhua; Zhai, Jiwei; Pan, Zhongbin; Shen, Bo
Abstract: In this work, [ x SrO, (1 −  x )BaO]-K2 O -Nb2 O5 -SiO2 (SBKNS, x   =  0.2, 0.4, 0.6, 0.8) glass-ceramics were synthesized through the controlled crystallization method. The phase structure, dielectric and energy-storage properties were systematically studied through the Sr substitution for Ba. It was found that the dielectric properties were improved due to the formation of solid liquid phase Sr0.5 Ba0.5 Nb2 O6 . Breakdown strength firstly increases and then decreases, which strongly depends on the variation in interfacial polarization. The highest value of breakdown strength reaches 1828 ± 88 kV/cm for x  = 0.4, which is attributed to more uniform and dense microstructure and lower interfacial polarization. Correspondingly, the optimized theoretical energy-storage density reaches up to 17.45 ± 0.74 J/cm 3 . The maximum of discharged energy-storage density of 1.45 J/cm 3 from P-E loop was acquired under electric field of 500 kV/cm. Moreover, discharged power density of the capacitor was evaluated and reached a high value of 1.76 MV/cm 3 in pulsed charged-discharged circuit.